alguém pode me ajudar
Anexos:
![](https://pt-static.z-dn.net/files/d91/7049c4fc6b0f01333f07bbe27821a9e9.jpg)
Soluções para a tarefa
Respondido por
0
Resposta:
g)
Respondido por
0
Resposta:
basta substituir:
g) se a = -2
(-2)^3 - 5 . (-2) ---> (-8) - (-10) = 2
h) se x = -3 e y = 5
(-3)^2 - 2 . 5 ---> 9 - 10 = -1
i) se a = -2 e b = -7
3 . (-2)^2 - (-7)2 ---> 12 - 49 = -37
j) se a = -3 e b = -4
5 . (-3)^2 + 3 . (-3) . (-4) ---> 45 + 36 = 81
k) se a = 2/3
(2/3)^2 + 4 . (2/3) ---> 4/9 + 8/3 = 28/9
Perguntas interessantes
Biologia,
7 meses atrás
História,
7 meses atrás
Matemática,
7 meses atrás
Português,
7 meses atrás
Química,
7 meses atrás
Matemática,
1 ano atrás
História,
1 ano atrás